Exploring the Possible Impact of Echocardiographic Diastolic Function Parameters on Outcome in Paediatric Dilated Cardiomyopathy - Sabrina Bressieux-Degueldre; Matthew Fenton; Troy Dominguez; Michael Burch (MDPI AG, 2022)
Diastolic dysfunction is an important determinant for prognosis and survival in several paediatric heart diseases. We aimed to explore its possible impact on outcome in children with dilated cardiomyopathy. From 2006 to 2016, children less than 18 years old with dilated cardiomyopathy were retrospectively enrolled. Echocardiographic diastolic function parameters and child outcomes were analysed. Of 43 children aged 0.2 to 16.1 years old referred with dilated cardiomyopathy, 8 patients required cardiac transplant or mechanical assist devices (18%), 24 had persistently abnormal left ventricular function and/or dilatation (56%) and 11 patients recovered (26%). There was no significant difference in mitral velocities on Tissue Doppler Imaging, mitral valve inflow velocities, isovolumic relaxation time, left atrial area z-score and mitral lateral E/e' ratios between patients with recovery and patients with disease progression or persistently abnormal ventricular function and/or dilation. This is the first study on childhood dilated cardiomyopathy to address individual echocardiographic diastolic function parameters and their association to recovery. In this study, echocardiographic parameters for diastolic function did not predict recovery.